A Critical Study of Comparative Education in The Middle East Countries; Ideological and Cultural - Zakki, Akhmad; Mahfud, Mohammad (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
As a center for Islamic studies, countries in the Middle East Region (including Saudi Arabia and Iran) have not been replaced in the eyes of Muslims, especially Indonesia. However, these students abroad do not only adopt their scientific studies, but they also tend to adopt the prevailing ideology and culture there which may not be fully applicable in Indonesia. This type of research is library research because it is entirely produced from literature studies, namely studying library materials/literature related to research problems. While the approach of this research is a descriptive qualitative approach, namely by describing the entry of ideology and culture from Saudi Arabia and Iran to Indonesia through graduates who have studied in these two countries. The purpose of this research is to find the problems and solutions of Saudi Arabian and Iranian graduates in the context of ideology and culture. The results of the research show that there are three things graduates from the Middle East including from Saudi Arabia and Iran can contribute positively to this nation, namely: first, emphasizing the values of love for local culture; secondly instilling religious insight as a whole; and third, negotiations between outside ideology and culture and local culture and ideology.Abstract:As a center for Islamic studies, countries in the Middle East Region (in this case including Saudi Arabia and Iran) have not been replaced in the eyes of Muslims, especially Indonesia. However, these students abroad do not only adopt their scientific studies, but they also tend to adopt the prevailing ideology and culture there which may not be fully applicable in Indonesia. This type of research is library research because it is entirely produced from literature studies, namely studying library materials/literature related to research problems. While the approach of this research is a descriptive qualitative approach, namely by describing the entry of ideology and culture from Saudi Arabia and Iran to Indonesia through graduates who have studied in these two countries. The purpose of this research is to find the problems and solutions of Saudi Arabian and Iranian graduates in the context of ideology and culture. The results of the research show that there are three things graduates from the Middle East including from Saudi Arabia and Iran can contribute positively to this nation, namely: first, emphasizing the values of love for local culture; secondly instilling religious insight as a whole; and third, negotiations between outside ideology and culture and local culture and ideology.